2020
DOI: 10.2139/ssrn.3555927
|View full text |Cite
|
Sign up to set email alerts
|

The Engagement-Diversity Connection: Evidence from a Field Experiment on Spotify

Abstract: It remains unknown whether personalized recommendations increase or decrease the diversity of content people consume. We present results from a randomized field experiment on Spotify testing the effect of personalized recommendations on consumption diversity. In the experiment, both control and treatment users were given podcast recommendations, with the sole aim of increasing podcast consumption. Treatment users' recommendations were personalized based on their music listening history, whereas control users w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
27
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(28 citation statements)
references
References 32 publications
0
27
1
Order By: Relevance
“…These features describe not only basic features of recorded music, such as its tempo and loudness, but also compound measures indicative of, for instance, a particular track's Danceability and Acousticness. This allows us to use Spotify as a platform for investigating sleep music in a representative industrialised population 27,28 .…”
Section: Introductionmentioning
confidence: 99%
“…These features describe not only basic features of recorded music, such as its tempo and loudness, but also compound measures indicative of, for instance, a particular track's Danceability and Acousticness. This allows us to use Spotify as a platform for investigating sleep music in a representative industrialised population 27,28 .…”
Section: Introductionmentioning
confidence: 99%
“…The average number of likes received on each user's comments is regarded as an indicator of information amplification. Holtz et al (2020) found that personalized recommendation increase user engagement after finishing a field experiment on Spotify. Thematic analysis is used to analyze engagement behavior on social platforms, and some content topics have been concluded.…”
Section: Related Workmentioning
confidence: 99%
“…Recent work has shed light on design features that moderate the relationship between social influence and diversity. In the context of music listening, Holtz et al [28] found that personalized recommendation decreased diversity within users, but increased diversity across users. Pescetelli et al [50] found that increased diversity increases collective intelligence for large groups (≈ 25 people) but decreases it for small groups (≈ 5 people).…”
Section: Quantifying Diversity and Divergencementioning
confidence: 99%
“…Social influence occurs when the decisions of a user are impacted by those of other users [10], and has been shown to be a key design dimension for contexts as varied as health behavior [9], political engagement [5] , collective behavior [41], online book purchasing [8], food ordering [30], and digital news engagement [46,62]. The ubiquity of social influence suggests how crucial a factor it is for platform designers seeking to jointly optimize for the quality and diversity of content online [28].…”
Section: Introductionmentioning
confidence: 99%